A qualitative study of blood and marrow transplant patient experiences participating in art making and music listening. (June 2016) - Mische Lawson, Lisa; Wedan, Lindsay; Stock, Morgan; Glennon, Cathy
Abstract: Purpose: To explore patient experiences of engaging in art making or music listening while receiving treatment in a blood and marrow transplant clinic. Method: Researchers recruited 25 individuals receiving blood and marrow transplant (BMT) treatment, 12 men and 13 women aged 22 to 74, from a Midwestern outpatient BMT clinic. Participants engaged in a painting activity or listened to music on an iPad using an internet music application for one hour. Researchers interviewed participants after the one-hour activity to gain insight into participants' perceptions of the art making or music listening experience. Interviews were recorded, transcribed verbatim, and independently coded by members of the research team. Researchers met on several occasions to analyse codes and agree on emerging themes. Results: Nine themes emerged from the data including, Engaging in Activity, Art and Music in Daily Life, Expression, Engaging with Equipment, Novelty, BMT Process, Activity Process, Social Support, and Living Situation . Participants enjoyed art making and music listening and found the activities beneficial during treatment. Conclusions: Participants benefited from art making and music listening because these activities increased the variety of options available during treatment, allowed for self-expression, and could be done alone or with caregivers. Highlights: Patients enjoyed the novelty of art making and music listening as diversion during lengthy BMT treatment. Both art making and music listening promoted self-expression in BMT patients. Relocating for treatment causes barriers to activity participation, so providing activities is helpful for this population.